Observations on Ceramium uruguayense (Ceramiaceae, Rhodophyta): first occurrence in the Caribbean Sea - Solé, María A. (HIDROBIOLÓGICA, 2017)
The red algae Ceramium uruguayense is reported for the first time in the Caribbean Sea. The vegetative and reproductive morphology of this species are described. Ceramium uruguayense is compared with other similar Caribbean species. Ceramium uruguayense has clear diagnostic characters like 8-9 periaxial cell, presence of pseudoperiaxial cells, acropetal direction in nodal formation and basipetal growth from periaxial cell. A distribution analysis of the genus in the Caribbean is presented.